Genetic relatedness among cultivars of the greek plum germplasm - Athanasiadis, Ioannis; Nikoloudakis, Nikolaos; Hagidimitriou, Marianna (My University, 2013)
Genetic diversity of the Greek plum germplasm collection was investigated using a combined RAPD and ISSR molecular markers approach. Twenty-six genotypes held at NAGREF-Naoussa were analyzed, producing in total 150 loci, of which 116 were polymorphic. Both techniques were highly informative and had a discrimination power greater than 0.9. RAPD and ISSR dendrograms were fairly correlated. The accessions were clustered according to ploidy and species. All Prunus domestica genotypes were grouped together and showed greater similarity to P. insititia and P. cerasifera genotypes compared to P. salicina, which was found genetically diverged. Bayesian structural analysis revealed significant admixture among genotypes. Greek varieties P. domestica 'Goulina' and 'Asvestochoriou' exhibited a distinctive genetic background, differentiating them from foreign varieties. This feature could make them attractive for breeding programs, since they can increase genetic diversity.
Keywords: Amova; Issr; Prunus spp.; Rapd; Structure